2017
DOI: 10.1080/09638288.2017.1397202
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity impairments in type 1 diabetes with long duration; common problems with great impact on daily life

Abstract: Compared to controls, patients with type 1 diabetes have a high prevalence of upper extremity impairments, often bilateral, which are strongly associated with activity limitations. Recognising these in clinical practise is crucial, and improved preventative, therapeutic and rehabilitative interventions are needed. Implications for rehabilitation Upper extremity impairments affecting the shoulder, hand and fingers are common in patients with type 1 diabetes, the prevalence being 2-4-fold higher compared to non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Controls received the same questionnaire except for diabetes-specific questions. The first part of the questionnaire was study-specific and has been described in a previous publication [20]. In brief, this part of the questionnaire contained issues on background characteristics such as weight, height, sex, diabetes duration, presence of diabetes complications such as retinopathy, UEIs, occupation, and work incapacity.…”
Section: Questionnairementioning
confidence: 99%
“…Controls received the same questionnaire except for diabetes-specific questions. The first part of the questionnaire was study-specific and has been described in a previous publication [20]. In brief, this part of the questionnaire contained issues on background characteristics such as weight, height, sex, diabetes duration, presence of diabetes complications such as retinopathy, UEIs, occupation, and work incapacity.…”
Section: Questionnairementioning
confidence: 99%
“…The prevalence of shoulder, hand, and finger impairments was 2-4 times higher in patients compared with controls, which was statistically significant for all investigated impairments ( Figure 4) 87 . One in five patients (21%) reported the absence of any of the five impairments or previous surgery.…”
Section: Prevalence Of Upper Extremity Impairmentsmentioning
confidence: 82%
“…All patients in the area were identified using the local diabetes registers and were invited to participate by a postal letter with a questionnaire enclosed. The questionnaire used has been described in detail in a previous publication, but in brief included self‐reported total daily insulin doses and method of administration, that is subcutaneously by either multiple daily injections (MDI) or continuous subcutaneous insulin infusion (CSII). Furthermore, background data such as weight, length, age, sex and age at diabetes onset as well as questions on presence of UEI including shoulder impairment (defined as pain and stiffness in shoulder), hand paraesthesia (defined as tingling or loss of sensation in the hand), hand stiffness (defined as stiffness in hand or forearm), finger locking (defined as finger locking in flexed position) and finger extend (defined as difficulty to extend one or several fingers) were included.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with T1D are commonly affected by upper extremity impairments (UEI) as stenosing tendovaginitis (trigger finger), carpal tunnel syndrome, limited joint mobility, Dupuytren's contracture and adhesive capsulitis (frozen shoulder) . In a population‐based cohort of patients with T1D and long diabetes duration, we recently reported that UEI are several folds more common and strongly associated with activity limitations in comparison with nondiabetic controls . The GH/IGF‐1 axis is involved in the regulation of the musculoskeletal system and connective tissue metabolism and both GH excess and GH deficiency have negative effects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation